Predictors of Renal Function in Primary Hyperparathyroidism - Walker, Marcella D. (Endocrine Society, 2014)
CONTEXT: Current guidelines for parathyroidectomy in primary hyperparathyroidism (PHPT) include an estimated glomerular filtration rate (eGFR) less than 60 mL/min per 1.73 m(2). Although the biochemical abnormalities associated with PHPT could impair renal function, there are currently no data examining whether more severe hypercalcemia, hypercalciuria, or nephrolithiasis are associated with chronic kidney disease (CKD) in mild PHPT. OBJECTIVE: This cross-sectional study evaluated predictors of renal function in PHPT. DESIGN: This is a case series of PHPT patients with (eGFR < 60 mL/min per 1.73 m(2)) and without (eGFR ≥ 60 mL/min per 1.73 m(2)) CKD. SETTINGS AND PARTICIPANTS: We studied 114 PHPT patients in a university hospital setting. OUTCOME MEASURES: We identified predictors of renal function using multiple linear regression. RESULTS: eGFR was associated with age, hypertension, antihypertensive medication use, fasting glucose, and 25-hydroxyvitamin D. eGFR was positively rather than negatively associated with several PHPT disease severity indices including history of nephrolithiasis, 24-hour urinary calcium excretion, and 1,25-dihydroxyvitamin D but not serum calcium or PTH levels. An eGFR less than 60 mL/min per 1.73 m(2) was observed in 15% (n = 17), all of whom had stage 3 CKD (eGFR 30–59 mL/min per 1.73 m(2)). Those with CKD were older, had higher 25-hydroxyvitamin D levels and lower 1,25-dihydroxyvitamin D levels, and were more likely to be hypertensive than those without CKD. There were no between-group (<60 vs ≥60 mL/min per 1.73 m(2)) differences in serum calcium, PTH, nephrolithiasis, or meeting surgical criteria other than eGFR. Multiple linear regression indicated that age and diastolic blood pressure were negatively associated with eGFR, whereas serum calcium, kidney stones, and alcohol use were positive predictors. Calculation of eGFR using either the Modification of Diet in Renal Disease or Chronic Kidney Disease Epidemiology Collaboration equation yielded similar results. CONCLUSIONS: PHPT patients with stage 3 CKD do not have biochemical or clinical evidence of more severe hyperparathyroidism compared with those without CKD. Traditional risk factors, rather than clinical or biochemical indices of PHPT, are associated with lower eGFR in mild PHPT.